Diagnosis of the reality of marketing knowledge management"A survey of the views of a sample of telecom operatorsIn the city of Sulaymaniyah " - يونس فراس رحيم; احمد عبد القادر رحومي (Journal of Economics and Administrative Sciences, 2011)
This research aimed to diagnose the perception based on Telecommunications of Iraq to the importance of activating knowledge management marketing in possession, as well as Indication of impediments to activate the management of marketing knowledge in the researched companies, also aimed to show the extent of the existence of significant differences in perception based on Telecommunications Iraqi importance of activating the management marketing knowledge in possession. To achieve the objectives of this research, the questionnaire was developed and distributed to a sample of telecommunications companies in the city of Sulaimaniya, was selected on the criterion according to the company’s life in terms of seniority in the telecommunications market. In order to achieve the objectives of the study, the questionnaire was developed and distributed to a sample of telecommunications companies in the city of Sulaimaniya, was selected on the criterion according to the company’s life in terms of seniority in the telecommunications market. The research found the following results: - Research has shown that the existing telecom companies are aware of the importance of activating knowledge management marketing in possession, as results showed intermediate levels of cognition. - Between research and there significant differences in perception based on the telecom companies to the importance of using knowledge management marketing in possession due to some personal variables and functional (academic qualification and years of work experience in marketing). - Research has shown the existence of a weak relationship between the independent variables of research and of (awareness of the importance of using knowledge management, marketing and use of constraints) in the possession of knowledge in marketing communications companies. Findings: Based on the results of the research has been to provide a number of recommendations and proposals, including the necessity of continuing the existing telecom companies are enabled marketing activities particularly with regard to the optimum use of the elements of the marketing mix and to achieve differentiation and the differences in services provided and motivate staff in the field of marketing.